2021
DOI: 10.1186/s13054-021-03574-w
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day progression of vital-sign circadian rhythms in the intensive care unit

Abstract: Background Disrupted vital-sign circadian rhythms in the intensive care unit (ICU) are associated with complications such as immune system disruption, delirium and increased patient mortality. However, the prevalence and extent of this disruption is not well understood. Tools for its detection are currently limited. Methods This paper evaluated and compared vital-sign circadian rhythms in systolic blood pressure, heart rate, respiratory rate and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Patients who died at the hospital ward showed no rhythmicity of respiratory rate and skin temperature, and a decrease of heart rate amplitude two days before death. This is in accordance with the observations of Davidson et al 2021 [ 21 ]. The decrease of circadian rhythm might be caused by several factors.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Patients who died at the hospital ward showed no rhythmicity of respiratory rate and skin temperature, and a decrease of heart rate amplitude two days before death. This is in accordance with the observations of Davidson et al 2021 [ 21 ]. The decrease of circadian rhythm might be caused by several factors.…”
Section: Discussionsupporting
confidence: 94%
“…Our study confirms the existence of a circadian pattern in vital signs of hospitalized COVID-19 patients. A study performed in multiple intensive care units demonstrated circadian patterns for blood pressure, heart rate, respiratory rate and temperature [ 21 ]. This study found that the difference between the peak and nadir of vital signs is reduced in patients who died compared to patients who recovered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients are not only more likely to suffer organ damage from the severity of their illness, but may be affected by poor light conditions in intensive care units (ICU) incompatible with maintenance of a healthy circadian rhythm ( Danielson et al., 2018 ). Ability to maintain physiological circadian rhythms has been associated with better outcomes in ICU ( Davidson et al., 2021 ), and could in principle, protect patients from circadian disruption and possibly altering the risk of PASC and ME/CFS.…”
Section: Me/cfs and Coronavirus Related Illnessesmentioning
confidence: 99%